Navigating a Component of Higher Education’s Hidden Curriculum: A Qualitative Study of First-Year Seminar Faculty and Students (Under Embargo) - Khoury, Matthew W. (My University, 2021)
This qualitative study was created to gain a better understanding of the impact of a for- credit first-year seminar course. Related existing research and theory included past studies on the first-year seminar, the hidden curriculum, and student persistence and retention. This study was intended to make an original contribution to the knowledge base through understanding the stories and narrated experiences of four faculty and six students involved with first-year seminars at a large university in the southeast. Three interviews were completed with my six student and four faculty collaborators. Transcripts were analyzed both with in vivo and emotion coding. Narrative profiles were created for each collaborator. Four main topics from student data were generated: sense of belonging, difficulty and feeling supported, pride and happiness, and academic rigor. Four main topics from faculty data were generated: building the foundation, structuring a first-year seminar, teaching a first-year seminar, and professors making meaning. Examples from the narrated experiences collaborators shared were provided to support each topic. Keywords: emotion coding, first-year seminar, hidden curriculum, in vivo coding, narrative inquiry, retention
Keywords: College dropouts--Prevention; College freshmen; Dissertations, Academic--United States; Education--Curricula; Emotions--Social aspects; Narrative inquiry (Research method)